근로자들의 건강증진 생활양식에 따른 구강건강 실천요인 - 송지연; 박지영; 김남송 (Han'guk Ch'iwisaeng Hakhoe chi, 2012)
Objectives : The purpose of this study was to examine the influential factors for the oral-health practice of adult workers and the relationship of their health-promotion life style to the factors of oral-health practice in an attempt to determine the impact of health-promotion life style. Methods : The subjects in this study were 160 workers who worked in Seoul, North-Jeolla and South-Jeolla Province, and were at the age of 20 and up. The survey was conducted from February 1 to July 20, 2011. Results : As for the relationship of the general characteristics of the workers to the factors of their health-promotion practice, gender made statistically significant differences to toothbrushing female (3.24),and there were statistically significant differences in education/concern according to more than college(2.72)scored higher academic credential(p＜0.05). The group of the workers whose health-promotion life style was better in terms of all the toothbrushing(3.35), use of oral hygiene supplies(2.19), regular dental-clinic visit(2.70), dietary control(2.84) and education/concern(3.20) scored higher, and there were statistically significant differences in the factors of education/concern(p＜0.05). Their health-promotion life style had an impact on regular dental-clinic visit among the factors of oral-health practice(p＜0.05), and there was a positive correlation between health- promotion life style and tooth brushing, dietary control(p＜0.05),regular dental-clinic visit, education and concern(p＜0.01) the factors of oral-health practice. Conclusions : Workers should be stimulated to get into sound life habits to change their behavior, and they should be urged to improve their preventive health care, to get a dental checkup and ultimately to promote their health as well. Companies should take measures to accelerate the oral health promotion of workers and provide more dental checkup programs for them to be more concerned about their oral health, to promote their oral health and to maintain the best oral health. KCI Citation Count: 3